Penerapan Model Cooperative Learning Tipe Teams Games Tournament (TGT) Untuk Meningkatkan Kemampuan Membaca Bahasa Arab Siswa Kelas VIII H Semester Genap Di MTs Darul Huffazh Pesawaran - Yuyun indrawati; Nurkholis; Heriansah (Program Studi Pendidikan Bahasa Arab, 2022)
Impact is that students often have difficulty understanding Arabic lessons and many of their reading abilities do not meet the Minimum Competency Standards (KKM), while the formulation of the problem in this study is